Mener une enquête ethnographique à distance et en présentiel : construction d’une méthodologie - Rosa Maria Bortolotti (Distances et Médiations des Savoirs)
This article presents feedback from an ethnographic approach carried out on a digital social network as part of doctoral research on the digital sociability practices of adolescents. Drawing from classical ethnography principles, it outlines the construction of the research protocol: the researcher’s presence on sociability platforms is not self-evident and raises ethical questions that must be addressed before proceeding with the research. Rather than advocating for a new form of field research, this article serves as an experimental and practical report intended to guide young researchers considering this type of online ethnography. It demonstrates that the use of digital social networks, particularly for those working with youth, constitutes a relevant complement to traditional field methods.